Analysis of extracellular metabolome by HS-SPME/GC–MS: Optimization and application in a pilot study to evaluate galactosamine-induced hepatotoxicity. (1st October 2018) - Araújo, Ana Margarida; Moreira, Nathalie; Lima, Ana Rita; Bastos, Maria de Lourdes; Carvalho, Félix; Carvalho, Márcia; Guedes de Pinho, Paula
Graphical abstract: Highlights: Development of two HS-SPME/GC-MS methods to detect a wide range of volatile compounds present in the cell exometabolome. These methods allowed a good separation between GalN exposed groups and controls. Various volatile compounds suffered significant alterations after GalN exposure. Our results suggest that GalN induces marked metabolic alterations in cells even at non-toxic concentrations. Abstract: Two methods based on headspace solid-phase microextraction (HS-SPME) coupled to gas chromatography–mass spectrometry (GC–MS) were developed to study in vitro the volatile exometabolome, which were then further tested in a pilot study to evaluate galactosamine-induced hepatotoxicity. The analysis of volatile organic compounds (VOCs) was carried out directly in the headspace of the cell culture medium, while some other volatile organic compounds such as volatile carbonyl compounds (VCCs) (aldehydes and ketones) were determined in the headspace of the cell culture medium after a previous derivatization step with O -(2, 3, 4, 5, 6-pentafluorobenzyl)hydroxylamine hydrochloride (PFBHA). Fiber selection was performed using a univariate mode, whereas a central composite design (CCD) was used in the optimization of several other parameters that affect the extraction conditions. VOCs showed optimal extraction results using a DVB/CAR/PDMS fiber, by adding 0.43 g of NaCl to a sample volume of 2 mL and allowing the sample to equilibrate for 10 min at 45 °C with a subsequent extraction for 39 min at the same temperature. For VCCs, the best extraction response was achieved after in-solution (2 mL) derivatization with 0.94 g L −1 of PFBHA (final concentration), followed by an incubation period of 6 min and an extraction time of 37 min at 53 °C, using a PDMS/DVB fiber. The applicability of both optimized methods was then tested, through a untargeted study, on cell culture medium samples obtained from primary mouse hepatocytes (PMH) exposed to three low concentrations (LC01, LC10 and LC30 ) of the well-known hepatotoxic agent galactosamine (GalN). The results obtained by both methods showed that volatile compounds from GalN exposed cells are separated from controls in a concentration-dependent manner. Several volatile compounds, namely aldehydes, ketones and alcohols, suffered significant alterations, suggesting that GalN induces marked metabolic alterations in cells even at low, non-toxic concentrations. Although preliminary, this metabolomics approach proved its potential to be used in future studies to evaluate toxicity of different xenobiotics.